2012
DOI: 10.1111/j.1526-100x.2012.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Invasive Shrub Honeysuckle Eradication Tactics for Amateurs: Stump Treatment versus Regrowth Spraying of Lonicera maackii

Abstract: Elimination of Asiatic shrub honeysuckles (Lonicera spp.) from preserves and conservation areas in eastern NorthAmerica is difficult because bird dispersal reintroduces seeds from shrubs in the neighborhood. To reduce this problem, honeysuckle control must be instituted on a broad scale and involve public participation. Many techniques for honeysuckle control are beyond the capabilities and inclinations of volunteers and local landowners. In a replicated study, we evaluated two suitable techniques and applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…While they saw similarly high levels of control (94% mortality), our study achieved equivalent levels of control with 30 and 60 g L −1 . Other studies have shown 90% to 100% efficacy in preventing resprouting within the year of treatment using ~88 g L −1 glyphosate (18%) in the cut stump method for controlling L. maackii, which is similar to what we achieved with our lower concentrations (Owen et al 2005;Schulz et al 2012). Use of the cut stump method with a 20% to 25% concentration of glyphosate (98 to 122 g L −1 ) is widely recommended to private landowners as a control technique (Miller et al 2013;Smith and Smith 2010).…”
Section: Resultssupporting
confidence: 87%
“…While they saw similarly high levels of control (94% mortality), our study achieved equivalent levels of control with 30 and 60 g L −1 . Other studies have shown 90% to 100% efficacy in preventing resprouting within the year of treatment using ~88 g L −1 glyphosate (18%) in the cut stump method for controlling L. maackii, which is similar to what we achieved with our lower concentrations (Owen et al 2005;Schulz et al 2012). Use of the cut stump method with a 20% to 25% concentration of glyphosate (98 to 122 g L −1 ) is widely recommended to private landowners as a control technique (Miller et al 2013;Smith and Smith 2010).…”
Section: Resultssupporting
confidence: 87%
“…Schulz et al (2012) found seasonal stem cutting, followed by an application of 18% glyphosate, resulted in a 75-85% reduction of L. maackii individuals, whereas stem cutting, followed by spraying of regrowth shoots with 1% glyphosate approximately 40 days later, was less effective, resulting in up to 56% of L. maackii individuals killed. Rathfon and Ruble (2007) tested four removal-treatment methods: foliar application, streamline basal bark application, full basal bark application, and stump cutting with a chemical application.…”
Section: Lonicera Maackii Effects On Ecosystem Processesmentioning
confidence: 99%
“…If the goal is to eliminate an exotic species, much of the work focuses on removal techniques (e.g. Batcher & Stiles ; Schulz et al ). We argue that emphasizing removal rarely accomplishes ecological control.…”
Section: Introductionmentioning
confidence: 99%